Cities, Words and Images - Lombardo, P. author. aut Link
XIII, 251 p.
Keywords: The city is an essential theme of modernity in literature, architecture, photography and film. This book first focuses on ardent reactions to the metropolitan explosion in the nineteenth century, with Baudelaire and Poe as key figures. More recent representations of the city are then investigated, in Europe and the United States. Lombardo reflects on the way in which the changes in human perception created by urbanization are expressed in the various arts, in terms of form and content.